Strategic Insights for Capacity Development on Forest Landscape Restoration: Implications for Addressing Global Commitments - Bloomfield, G.; Meli, P.; Brancalion, Pedro H.S.; Terris, E.; Guariguata, Manuel R.; Garen, E. (SAGE Publications, 2019)
Global initiatives such as the Aichi Targets and Bonn Challenge have inspired governments to pledge to restore millions of hectares of degraded lands. Many of these calls to action and policy frameworks identify capacity development as important for implementing and scaling-up restoration activities to meet global targets. However, there is little explanation about what capacity development actually involves. How is capacity development approached in the context of restoration? What makes it more or less effective? This article aims to help fill that gap by identifying four components of what an effective approach to capacity development might look like, drawing upon a number of examples in practice. We believe that capacity development initiatives can more effectively support stakeholders to address the complex nature of forest landscape restoration (FLR) if they include the following four components: (a) activities tailored to stakeholder needs and context, (b) knowledge and applied experience from diverse sources and disciplines, (c) skill sets for selecting among a suite of restoration interventions, and (d) inclusion of multiple subjects and skill sets (e.g., social, financial, legal, etc.) in addition to technical or ecological themes. As exemplified by the organizations discussed in this article, these four elements of capacity development can help to support restoration professionals and other stakeholders to think holistically, moving from the scale of an individual farm or plot to the landscape scale where they must address more diverse stakeholder interests, societal trade-offs, and socioecological heterogeneity. This more holistic approach to FLR planning and implementation is needed to more effectively accomplish ambitious FLR targets worldwide.